2017
DOI: 10.1177/0884533617698098
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength and Malnutrition (Undernutrition) in Hospitalized Versus Nonhospitalized Children Aged 6–14 Years

Abstract: HGS was not significantly different between hospitalized and nonhospitalized participants, although anthropometric measurements were similar between groups. A strong relationship was demonstrated between HGS and BMI and MUAC z scores. Further research is needed that examines serial HGS measurements, feasibility in hospitalized patients, and the association of HGS measurements and nutrition risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…It has been concluded that, among children and adolescents, handgrip strength can better assess malnutrition and it may be a potential marker of undernutrition in hospitalized patients [26]. Adolescent girls with low weight obtained lower levels of handgrip strength compared to girls with normal weights [33]; however, other studies found no differences in handgrip strength among female adolescents with low weight or normal weight, as well as those who are overweight [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been concluded that, among children and adolescents, handgrip strength can better assess malnutrition and it may be a potential marker of undernutrition in hospitalized patients [26]. Adolescent girls with low weight obtained lower levels of handgrip strength compared to girls with normal weights [33]; however, other studies found no differences in handgrip strength among female adolescents with low weight or normal weight, as well as those who are overweight [34].…”
Section: Discussionmentioning
confidence: 99%
“…Scores of 0 or 1 in the http://dx.doi.org/10.1590/1678-9865202033e190154 CONUT are considered normal values and values equal or greater than 2 might be taken as evidence of different levels of undernutrition. Therefore, to discriminate the existence of undernourishment, our subjects should meet at least one of the following criteria: value <-1.00 in BMI Z-score [18,19,26]; value <15th percentile in the fat and/or fat-free mass corresponding to their gender and age [27]; and/or score ≥2 in the CONUT [5].…”
Section: E T H O D Smentioning
confidence: 99%
“…The movement was repeated 3 times for both hands and the obtained value was recorded and averaged. 10 To understand the dominant hand, the child was asked to write her/his name in the air, and whichever hand she wrote, that hand was recorded as dominant. 10…”
Section: Anthropometrymentioning
confidence: 99%
“…9 Although there are no reference values for children yet, the use of HGS over 6 years old is recommended by the ASPEN. 10,11 This study was planned and conducted as controlled, cross-sectional research to compare HGS of malnourished adolescents with adolescents with normal nutritional status who were referred to the pediatric gastroenterology outpatient clinic.…”
mentioning
confidence: 99%
“…Measurement of HGS is non-invasive, simple, and affordable. It may enable the investigation of acute changes in nutritional status and evaluation and prognosis of muscular strength in juvenile idiopathic arthritis, congenital myotonic dystrophy, and traumatic hand injuries [ 16 , 17 , 18 , 19 ]. Children’s height, weight, muscular mass, and bone density all impact HGS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%